2007
DOI: 10.2139/ssrn.964722
|View full text |Cite
|
Sign up to set email alerts
|

Productivity, Technical Efficiency, and Farm Size in Paraguayan Agriculture

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
18
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 21 publications
(24 reference statements)
5
18
0
3
Order By: Relevance
“…Both farm size and number of plots showed a negative correlation with crop yield in the first phase (imperial and communist). This corresponds to the work of Masterson (2007) in the Paraguayan -and Dessalegn (1984) in the Ethiopian -Agriculture that they found an inverse relationship between farm size and crop yield. Only 1.2 percent (R 2 = 0.012) and 3 percent (R 2 = 0.03) of the yield variation was explained by a variation in farm size and land fragmentation respectively.…”
Section: Growth In Crop Yield and Livestock Numbersupporting
confidence: 82%
“…Both farm size and number of plots showed a negative correlation with crop yield in the first phase (imperial and communist). This corresponds to the work of Masterson (2007) in the Paraguayan -and Dessalegn (1984) in the Ethiopian -Agriculture that they found an inverse relationship between farm size and crop yield. Only 1.2 percent (R 2 = 0.012) and 3 percent (R 2 = 0.03) of the yield variation was explained by a variation in farm size and land fragmentation respectively.…”
Section: Growth In Crop Yield and Livestock Numbersupporting
confidence: 82%
“…Many studies have concluded that the larger farm size is preferable to smaller farm size in terms of outputs obtainable from the production process (Hassan and Ahmad, 2005;ibid). However, findings of other investigators in the same area assert otherwise (Badunenko et al, 2006;Masterson, 2007). Their conclusive assertions lend credence that farms with smaller land sizes produce higher output than their larger size counterparts.…”
Section: Introductionmentioning
confidence: 89%
“…That is to say how much is obtained from a parcel of land is a function of several factors rather than just the number of acreages engaged. Additionally, in making a case for either of them, there is always some unintended neglect of the influences of other factors of production in the production process which may lead to erroneous conclusions of one being preferable to the other (Masterson, 2007). Conventionally, age and experience are directly proportional in the smallholder farmer operations.…”
Section: Introductionmentioning
confidence: 99%
“…Hasil penelitiannya menemukan bahwa kredit, jumlah tenaga kerja, luas lahan teririgasi mempengaruhi produktivitas lahan pertanian. Masterson (2007) melakukan penelitian produktivitas lahan, efisiensi teknis dan skala ukuran tanaman pangan pada sektor pertanian di Paraguay. Hasil penelitiannya dengan menggunakan model regresi berganda ditemukan variabel luas lahan yang dikuasai berpengaruh negatif terhadap produktivitas lahan.…”
unclassified